Cylindrocystis Menegh. (Chlorophyta) - A new record for Bangladesh (Bangladesh Journal of Botany, 2008)
Cylindrocyctis brebissonii Menegh. and C. crassa var. elliptica West and West have beenillustrated and discribed in this paper as new report for Bangladesh. Key words: Phytoplankton, Cylindrocystis brebissonii, Cylindrocystis crassa var. elliptica, Saccoderm desmid, New record, Bangladesh doi:10.3329/bjb.v37i2.172 Bangladesh J. Bot. 37(2): 189-191, 2008 (December)